Relationship between motivation and satisfaction in whitewater rafting activity - Samat Hajar Asmidar, Mohd Rasyid Nelfianty, Azizuddin Khan Thariq Khan (Universiti Pendidikan Sultan Idris, 2016)
Relationship between motivation and satisfaction in whitewater rafting activity by Samat Hajar Asmidar, Mohd Rasyid Nelfianty, Azizuddin Khan Thariq Khan,